UNIT 1.1 Volume Measurement. Issue 10 (1st May 2015) - Davis, Thomas; Zanella, Andrew
Abstract : This unit describes the common types of volumetric apparatus used in the life science laboratory, their use, and care. When an experimenter needs to prepare solutions at accurate concentrations and quantitatively transfer samples of liquid from one container to another, an array of glassware and plasticware is available for these operations ranging from a microliter to more than a liter in volume. Considerations of temperature, solvent compatibility, and safety also need to be taken into account. © 2015 by John Wiley & Sons, Inc.